居延漢簡과 傷寒論의 病症 비교 연구 - 하기태(Ki Tae Ha); 정한솔(Han Sol Jeong); 신상우(Sang Woo Shin) (동의생리병리학회지, 2011)
More than 30,000 Wooden Slips were excavated in the Juyan region in 1930s and 1970s. These slips recorded military actions of Juyan Frontier Fortress during Han dynasty, which is about BC 100 ~ AD 30. On the slips, there are many disease names and symptoms mentioned. We focused on a certain disease name, namely, Shnaghan(傷寒; injured by cold), which is the main subject of Shangha-lun(傷寒論). Looking closely into these Juan Wooden Slips, we found many articles recording Shanghan, including related diseases and symptoms, such as Shanghan(傷汗; injured by sweat), headache, fever and chills, immobilization of limbs, unacceptance of foods. And there are another Shanghan-related symptoms, such as inflation of upper-abdomen(心腹支滿), pain of upper abdomen(心腹痛), strain of both armpits(兩胠葥急), inflation of chest(胸脇支滿), tightness and fear in the chest(煩滿). Although they have no direct relationship with Shanghan, there are many symptoms, including the external wounds of waist, finger, thigh, back, breast and head, abscess of leg and elbow, sore throat, itching, leucorrhea, powerlessness of hands and legs(手足癃), visceral injury(傷臟), tinnitus, cold, warm and heat. Because the Wooden Slips are very short, with some characters even missing, we can not confirm the detail of the disease and symptoms. In addition, we will report about the herbal medicines and other treatments, which are recorded on the slips, by further research. KCI Citation Count: 1